IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL THROUGH CONTEXTUAL APPROACH TO IMPROVE THE ACTIVITY AND STUDY RESULT - Suryani T, Andi Lilis; Hasri, Hasri; Sugiarti, Sugiarti (JCER (Journal of Chemistry Education Research), 2017)
This Classroom Action Research (CAR) aimed to know how to implement the steps of Guided Inquiry learning Model through Contextual Approach to improve the activity and study results of the Student of Class XI IPA3 of SMAN 7 Pinrang. This research was held by two cycles. Research result data show the average percentage of student learning activities the first cycle were 46. 80% in less active category and the second cycle were 69.28% in active category andcompleteness class percentage the first cycle were 33.33% not complete category and the second cycle were 83.33% with complete category. It can conclude that the steps of guided inquiry learning model through contextual approach can be improve the activity and study result of SMAN 7 Pinrang student.